New Efficient 1, 1′‐Bi‐2‐naphthylamine‐Based Hole‐Transporting Materials for Perovskite Solar Cells. Issue 16 (1st June 2017) - Zong, Xueping; Qiao, Wenhua; Chen, Yu; Wang, Hui; Liu, Xu; Sun, Zhe; Xue, Song
Abstract: Two new efficient hole transporting materials (HTMs) Q216 and Q219 based on C2‐symmetric 1, 1′‐bi‐2‐naphthylamine central core have been synthesized. The bis(4‐methoxyphenyl)amine‐substituted 9H‐carbazole were chose as end groups to link with the central core. The two HTMs have suitable molecular orbital energy levels, being well matched with that of CH3NH3PbI3 and carbon counter electrode. By introducing bis(4‐methoxyphenyl)amine unit (BMPA) to "3" position in carbazole donor, Q219 exhibits smaller dihedral angle between carbazole and naphthyl unit than Q216 with "2"‐BMPA, which may improve the electron donor ability of carbazole and favors to charge transport. The highest power conversion efficiency of PSC based‐Q219 is 9.31 %. EIS and IMVS measurements confirm that Q219 reduces charge recombination in perovskite solar cells (PSCs). Accordingly, the PSC with Q219 favors a 99 mV higher open circuit voltage than that of the Q216. The results provide some useful ideas to further design more promising structure of HTMs. Abstract : New 1, 1'‐bi‐2‐naphthylamine‐based hole‐transporting materials can flexibly control photovoltaic parameters of perovskite solar cells (PSCs) by introducing bis(4‐methoxyphenyl)amine unit (BMPA) to "2" and "3" position in carbazole donor. PSC based on Q219 bearing "3"‐BMPA units achieves a PCE of 9.31 %, yielding a Voc of 949 mV, a Jsc of 17.33 mAcm‐2 and a FF of 0.57. Thanks to longer electron lifetime and lower charge recombination of Q219‐based devices. Q219 also offers a 99 mV higher Voc without the loss of Jsc.